Orientación familiar en el desarrollo de la autonomía de los niños de 4 años de educación inicial de la Unidad Educativa “Padre Marcos Benetazzo - Kanki Lamilla, Elvis Junior (2023)
The study carried out at the "Padre Marcos Benetazzo" Educational Unit focused on analyzing the impact of family orientation on the development of autonomy of 4-year-old children in the context of initial education. A mixed research approach was used that combined qualitative and quantitative methods, to obtain a complete understanding of the subject, through a non-experimental design, the variables and relationships were observed in their natural environment. The scope is documentary and descriptive to collect information. The analytical-synthetic method made it possible to analyze quantitative data, and the questionnaire survey technique served as the main instrument to assess the knowledge and perceptions of teachers and representatives about family orientation and autonomy. The findings of this research highlight and support the need to promote parenting practices that foster autonomy. In addition, they underline the importance of collaboration between the school and parents to provide an optimal environment for the development of children at this crucial stage. It is concluded that the majority of those surveyed recognize the importance of parental participation in the education of 4-year-old children to promote their autonomy.